Compression and mechanical connectors for power cables. Test methods and requirements for compression and mechanical connectors for power cables for rated voltages up to 1 kV (U m = 1, 2 kV) tested on non-insulated conductors Part 1-1, (30th September 2019) - British Standards Institution,
No abstract available